Effect of Red Dragon Fruit Extract (Hylocereus polyrhizus) on MDA Metabolite Products and CD36 Expression in Artery Carotid Communis Mice (Mus muscullus) Fed a High-Fat Diet - Larasati, Galuh Wiedani Kusuma Dyah; D.K. Wardani, Lailia; Legowo, Djoko (Universitas Syiah Kuala, 2024)
Red Dragon fruit (Hylocereus polyrhizus) has the potential for the prevention of diseases associated with inflammatory and oxidative processes such as cardiovascular diseases due to the presence of their antioxidant compounds including phenols, flavonoids, tocopherol, ascorbic acid, thiamin, niacin, riboflavin, minerals, betacyanin, -carotene, lycopene, p-coumaric acid, protocatechuic acid, vanillic acid, gallic acid, syringic acid, and p hydroxybenzoic acid. Antioxidant compounds can prevent the atherogenesis process by reducing MDA metabolite products and CD36 expression in artery carotid communis. MDA metabolite products are indicators of lipid peroxidation, while CD36 expression is a scavenger receptor which responsible for the retention and absorption of LDL-Ox in macrophages and endothelial cells. This study aimed to prove the effect of red dragon fruit extract in reducing MDA metabolite products and CD36 expression in artery carotid communis of mice fed a high-fat diet. This research was in vivo experimental study with a randomized post test only control group design. This research used 40 male mice which were divided into five groups, namely negative control K0 (without high fat diet and extract), positive control K1 (high fat diet without extract), P1 (5mg extract/mice/day), P2 (extract 10mg/mice/day), P3 (extract 20mg/mice/day). A high fat diet was given for 56 days. Red dragon fruit extract was given for 28 days. At the end of the study, all mice were euthanized and their artery carotid communis were taken for immunohistochemistry staining. MDA and CD36 expression measurements were carried out using the Immune Reactive Score (IRS), which is the result of multiplying the percentage of immunoreactive cells (A) with the color intensity score (B) of immunoreactive cells.